Hybridity on Architecture and Urban Spaces in the Colonial Tin Mining Town of Muntok-Bangka - Kurniawan, Kemas Ridwan; Kusumawardhani, Ratu Arum; Ellisa, Evawani; Widyarta, Muhammad Nanda (Makara Human Behavior Studies in Asia, 2013)
This paper concerns the importance of socio-cultural hybridity in the process of architecture and urban development. It confronts spatial particularity occurring between the discourses of colonialism and multiculturalism. As a result of centuries of dynamic interaction amongst several ethnic groups including Malay, Chinese and European, Muntok as the colonial capital town of Bangka Island before 20thcentury offers various architectural edifices and urban forms. The scope of this paper focuses on the intersection between colonial history and hybridity itself and the research analyses its material represent through architecture and urban form. The methods of the research are conducted through a combination of a qualitative and a quantitative approach involving direct interviews, data collection, and typological analysis. Hybridity becomes a critical tool to reveal the dynamic process of architecture and urbanism. The research found that hybrid architecture is not only about the existence of physical aspects of buildings, but also most importantly about the integration and dialectical relationship between its materiality and the socio-cultural processes that lie behind it.